PENGEMBANGAN APLIKASI GAME JEGEG BAGUS BALI UNTUK MEMPERKENALKAN TAHAPAN UPACARA MANUSA YADNYA BERBASIS ANDROID - I Gede Agung Purnama Putra; I Gede Mahendra Darmawiguna; I Made Gede Sunarya (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2015)
The aimed of this game are (1) Designing game "Jegeg Bagus Bali" tointroduce the Manusa Yadnya ceremony in Bali based on Android system. (2) Implementation the game "Jegeg Bagus Bali" to Recognition of Manusa Yadnya ceremony in Bali based on Android system.This application is developed by using the Waterfall method and implemented in the Java programming language using Eclipse editor. The main feature of this application is the game to treat character that was chosen and playing the character until it reaches the final stage of Manusa Yadnya ceremony. The development of this application, it will be easier to introduce Manusa Yadnya in society.The result of this game shows that “Jegeg Bagus Bali” application can running at all of the Android software according to minimum necessary application that was determined. And all of the feature that occur in this “Jegeg Bagus Bali” application can running well as their functions.